Analysis of International Tourism Demand in Indonesia: An Ordinary Least Square (OLS) Approach - Wasiaturrahma, Wasiaturrahma; Rohmawati, Hilda (Universitas Negeri Semarang, 2021)
The demand for tourism in Indonesia which continues to increase every year is actually still not able to reach the predetermined target. In the Other hand there is still no research comparing proxies for calculating tourism prices (exchange rates and relative prices) in one study. The calculation of substitution prices for each of the countries studied tends to be the same. But each country has different characteristics and different tastes, so the country of substitution must be distinguished for each country. This study analyzes the demand for international tourism in Indonesia with 106 countries visiting Indonesia the most. The data used in this study is cross section data in 2018. The analytical technique used in this study is OLS. This study uses two models, namely model 1 using relative prices as a proxy for tourism prices and model 2 using exchange rates with cross exchange rate calculations as proxies for calculating tourism prices. Relative price is considered a suitable variable to be used as a proxy for calculating tourism prices because it takes into account the CPI for each country. The model that includes the relative price variable also has a higher goodness of fit, so the relative price can be used as a proxy for tourism prices